Cobalt-Catalyzed Chelation-Assisted Alkylation of Arenes with Primary and Secondary Alkyl Halides - Gao, Ke; Yamakawa, Takeshi; Yoshikai, Naohiko (Synthesis, 2014)
Cobalt–N-heterocyclic carbene catalytic systems have been developed for chelation-assisted ortho-alkylation of aromatic compounds with alkyl halides. Aryl imines can be selectively monoalkylated at room temperature by various primary or secondary alkyl chlorides or bromides. The catalytic system can also be applied to 2-arylpyridine derivatives, which in the absence of steric hindrance are amenable to dialkylation by an excess of the alkyl halide. Mechanistic experiments, including reactions of stereochemical probes and radical clocks, indicate that the reaction involves single-electron transfer from the cobalt center to the alkyl halide to form the corresponding alkyl radical, which has a finite lifetime before it undergoes C–C bond formation.
Keywords: functionalization; catalysis; cobalt; alkylations; alkyl halides; radical reaction